Pls answer.

Asked by  | 4th May, 2009, 08:17: AM

Expert Answer:

 x =(2008)1004 + (2008)-1004 and y = (2008)1004 - (2008)-1004

(x2 - y2) = ( x + y) ( x - y ) =  ((2008)1004 + (2008)-1004 + (2008)1004 - (2008)-1004 )  ((2008)1004 + (2008)-1004 -                                                ((2008)1004 - (2008)-1004))

                                         = ((2008)1004 + (2008)-1004 + (2008)1004 - (2008)-1004 )  ((2008)1004 + (2008)-1004          

                                            -(2008)1004 + (2008)-1004 )

                                        = (2 X (2008)1004 ) (2 X (2008)-1004 )

                                       =  4

Answered by  | 4th May, 2009, 12:01: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.